2015
DOI: 10.1167/iovs.15-17137
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickness in Children: The Shandong Children Eye Study

Abstract: PURPOSE.To examine the thickness of the macular choroid and its associations in school children aged 6 to 18 years. METHODS.The school-based cross-sectional Shandong Children Eye Study included 6026 (94.7%) of 6364 eligible children fulfilling the inclusion criterion of an age from 4 to 18 years. Spectral-domain optical coherence tomography (SD-OCT) was performed for a subgroup of 972 school children aged 6þ years. All participants underwent ocular examinations, including measurement of visual acuity, cyclople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
44
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 35 publications
10
44
3
Order By: Relevance
“…8,12,14 The choroid in the macular region was thickest in the temporal sector and thinnest in the nasal sector, which was similar to that in previous studies carried out in pediatric populations. 7,8,[10][11][12][13]15 The mean global PPCT in our study (136 6 33 lm) was also smaller than the mean PPCTs reported by a previous study (165 6 34 lm). 22 Age, race, refractive status as well as the instruments and protocols used may contribute to these differences.…”
Section: Varied Cht At the Posterior Polecontrasting
confidence: 77%
“…8,12,14 The choroid in the macular region was thickest in the temporal sector and thinnest in the nasal sector, which was similar to that in previous studies carried out in pediatric populations. 7,8,[10][11][12][13]15 The mean global PPCT in our study (136 6 33 lm) was also smaller than the mean PPCTs reported by a previous study (165 6 34 lm). 22 Age, race, refractive status as well as the instruments and protocols used may contribute to these differences.…”
Section: Varied Cht At the Posterior Polecontrasting
confidence: 77%
“…Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlesupporting
confidence: 69%
“…In 2015, Zhang et al (22) reported the results of a study on 972 children aged 6 to 18 years, irrespective of refractive errors, including high myopia and high hyperopia, and also found an inverse correlation between axial length and ChT. However, contrary to other authors, they found a decrease in ChT with age in children.…”
Section: Discussionmentioning
confidence: 95%
“…Since the development of enhanced depth imaging optical coherence tomography (EDI-OCT)7 and more recently, swept-source optical coherence tomography (SS-OCT)8 which has enabled the in vivo imaging and measurement of the choroid, the characteristics of the choroid under normal8910111213141516171819202122232425262728293031, as well as under certain pathologic conditions323334353637, have been described. Age89101117, refractive error and axial length (AL)811131417383940 have been well established as major factors that can impact in vivo choroidal thickness in healthy adults, with increasing age, AL and decreasing refractive diopter being associated with a reduction of choroidal thickness.…”
mentioning
confidence: 99%